- liftU :: UId m => (UGenId -> a -> UGen) -> a -> m UGen
- liftU2 :: UId m => (UGenId -> a -> b -> UGen) -> a -> b -> m UGen
- liftU3 :: UId m => (UGenId -> a -> b -> c -> UGen) -> a -> b -> c -> m UGen
- liftU4 :: UId m => (UGenId -> a -> b -> c -> d -> UGen) -> a -> b -> c -> d -> m UGen
- liftP :: (a -> IO UGen) -> a -> UGen
- liftP2 :: (a -> b -> IO UGen) -> a -> b -> UGen
- liftP3 :: (a -> b -> c -> IO UGen) -> a -> b -> c -> UGen
- liftP4 :: (a -> b -> c -> d -> IO UGen) -> a -> b -> c -> d -> UGen

# Documentation

liftU2 :: UId m => (UGenId -> a -> b -> UGen) -> a -> b -> m UGenSource

Lift base UGen to monadic form.

liftU3 :: UId m => (UGenId -> a -> b -> c -> UGen) -> a -> b -> c -> m UGenSource

Lift base UGen to monadic form.